Global and Regional Spillovers to Pacific Island Countries - Wu, Yiqun (IMF Working Papers; Working Paper ;, 2012)
Regional integration of Pacific Island countries (PICs) with Australia, New Zealand, and emerging Asia has increased over the last two decades. PICs have become more exposed to the region's business cycles, and spillovers from regional economies are more important for PICs than from advanced economies outside the region. While strong linkages with Asia would help in the event of a global downturn, PICs remain particularly vulnerable to global commodity price shocks. In this paper, we use a Vector Error Correction Model (VECM) for each PIC to gauge the impact of global and regional growth spillovers. The analysis reveals that the impact on PICs' growth from an adverse oil shock would be substantial, and in some cases even larger than from a negative global demand shock. We also assess the spillovers to the financial sector from the deterioration of the global outlook. PICs should continue to rebuild policy buffers and implement growth-oriented structural reforms to ensure sustained and inclusive growth.